The Benefits of Adopting Sustainable Electronic Health Records (EHR) for Healthcare Providers: A Systematic Literature Review - Ahmad Said; Yulita Hanum P Iskandar (Universitas Pasundan, 2024)
Electronic health records (EHRs) are being quickly used by healthcare global organizations. One of the primary goals of EHR implementation is to improve healthcare efficiency and workflow. Nonetheless, the effect of EHRs on healthcare efficiency and workflow is currently under investigation. Thus, the objective of this systematic literature review is to explore the impact of EHRs on healthcare efficiency and workflow improvement. A comprehensive search of four internet databases yielded 35 relevant articles published between 2017 and 2022. In terms of inclusion, 94 articles were initially identified from Scopus and Web of Science (WoS), and ultimately, only 38 articles were selected for this study based on abstract comparison. Then, in terms of exclusion, a further selection was made using the comparison of the introduction sections of each article, resulting in 35 articles being used in this research. The research was reviewed using a qualitative synthesis method, which enabled the identification of common themes and patterns. This systematic literature review adhered to the guidelines provided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). The number of participants in the articles based on geography is from 13 countries, with the highest total in the US, amounting to 19 articles, and the lowest at 1 article distributed across 7 countries. EHRs can improve healthcare workflow and efficiency in several ways, according to the findings of this study.